A Study of Chemical Constituents in Platinum Fast-Grown Teak Wood (Tectona grandis) with Age Differences Using Py-GCMS Coupled with Interdependence Multivariate Analysis - Maya Ismayati; Dwi Ajias Pramasari; Wahyu Dwianto; Danang Sudarwoko Adi; Nyndia Tri Muliawati; Ratih Damayanti; Narita Ayu Putri Pramesti; Syahrul Ramadhan; Ari Hardianto; Nadia Nuraniya Kamaluddin (HAYATI Journal of Biosciences, 2023)
Pyrolysis gas chromatography-mass spectrometry (Py-GCMS) is a simple, rapid, and reliable analytical technique to assay lignocellulose biomass. This study aims to analyze the chemical content of various ages of platinum fast-grown teak wood using PyGCMS coupled with interdependence multivariate analysis. Fifty-eight peaks were shown in the pyrogram originating from carbohydrates, lignin, and extractive derivatives. Along with age, platinum fast-grown teak wood showed higher carbohydrate derivatives in heartwood than sapwood. Compared to teak wood grown in conventional (between 36.72-45.69%), platinum fast-grown teak wood has a higher content of carbohydrates (42.82-48.04%). A substantial amount of G-unit lignin was detected in the sapwood, while the S-unit lignin dominated the heartwood. The extractive content of 10-years-old teak wood heartwood was 4.82%, higher than 10- and 20-years-old heartwood from conventional wood (2.23% and 8.88%, respectively). Multivariate analysis of the chemical compound showed that Py-GCMS could be utilized to classify platinum fast-grown and conventional teak wood. 2-methyl anthraquinone (MAQ) content of 10-year-old fast-grown teak wood was 2.5 times higher than 20-year-old conventional teak wood. Based on the study, platinum fast-grown teak wood is promising as alternative wood material to fulfill the market demand for conventional teak wood.